Cardiovascular changes in patients with mild‐to‐moderate chronic kidney disease compared with healthy subjects: a 5‐year follow‐up study. (22nd November 2019) - Asp, Anna M.; Wallquist, Carin; Rickenlund, Anette; Hylander, Britta; Jacobson, Stefan H.; Caidahl, Kenneth; Eriksson, Maria J.
Summary: Background: There is limited knowledge about how cardiovascular parameters change over time in patients with mild‐to‐moderate chronic kidney disease (CKD). We studied several cardiovascular biomarkers over a 5‐year period in patients with mild‐to‐moderate CKD and in healthy controls. Methods: Fifty‐four patients with CKD stages 2–3 and 54 controls were included. The CKD patients were closely monitored and well controlled for hypertension and other cardiovascular risk factors. Ambulatory blood pressure (BP) monitoring, ankle–brachial index (ABI), carotid and cardiac ultrasound (including measurement of the left ventricular mass index (LVMI)), and biochemical analyses were evaluated. Results: Renal function decreased in both groups, with no significant difference in the change over time. In the CKD patients, none of the BP variables increased over time, but in the controls, average 24‐h and daytime systolic BP increased significantly. ABI increased slightly in the CKD patients ( P <0·001), but not in the controls ( P  = 0·963), and phosphate had a significant positive effect on ABI. Although in the CKD patients, there was no significant increase over time in common carotid artery diameter ( P  = 0·274), there was a small but significant increase in the controls ( P  = 0·001). LVMI increased significantly over time in both groups. Conclusions: In our study of patients with mild‐to‐moderate CKD, the progression of cardiovascular changes over time was relatively slow. Good BP control and treatment of other risk factors may have contributed to slow the progress of cardiovascular involvement, which emphasizes the importance of dedicated care in this population.